ANALYSIS OF VILLAGE FUND MANAGEMENT DURING THE COVID-19 PANDEMIC IN PANCURAN VILLAGE, SOUTH SUWAWA DISTRICT - Podungge, Abdul Madjid (Universitas Negeri Gorontalo, 2023)
This article aims to analyze and describe the Village Fund governance process during the Covid-19 Pandemic in Pancuran Village, South Suwawa District. The method used in this article is a qualitative descriptive method, using adata analysis which is an interactive model analysis consisting of three components of analysis namely: 1) Data reduction; 2) Presentation of data; 3) Verification of Data and Conclusion Drawings. The results of the article show that: 1) The transparency of village fund management during the Covid-19 pandemic in Pancuran Village has proven to be quite effective. This is due to the monitoring system carried out by various parties ranging from the Village Consultative Board, Village Facilitators, the Audit Board of the Republic of Indonesia, and the community. 2) Accountability of village fund management during the Covid-19 pandemic in Pancuran village has not been optimal. This is due to the budget shift policy during the Covid 19 pandemic which did not touch all communities who were entitled to receive BLT Village Funds. 3) Participation in village fund management during Â the Covid-19 pandemic in Pancuran village has not been optimal, because the village government has not been optimal in updating DTKS data to identify people who are eligible to receive BLT, subsidies, capital assistance and various other programs; 4) The principle of order and budget discipline during the Covid-19 pandemic in Pancuran Village has been running well, caused by village apparatus management that continues to coordinate BLT budget shifts during the pandemic.